2020
DOI: 10.3390/ma13235454
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Gypsum Materials with Potential Use for Thermal Insulations

Abstract: This article presents the influence of three additions i.e., hydroxyethyl methyl cellulose (HEMC), sodium bicarbonate and flue gas desulfurization (FGD) gypsum on the porosity of gypsum-based materials. The specific microstructure for a material with good thermal insulation properties i.e., numerous closed pores distributed in the binding matrix, was achieved using HEMC (0.3 wt.%) and sodium bicarbonate (0.5–2 wt.%). The addition of HEMC to the gypsum binder determines, as expected, an increase of the porosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Evans et al [12] developed a new method for the preparation of semi-dry plaster mortars, which incorporated expanded perlite with glass fibers. The fact that these lightened plaster materials are easily applicable on site and have good thermal resistance leads to their incorporation as rehabilitation materials, even improving the results obtained with porous materials made with Portland cement [13]. Finally, we find authors who have focused their research on reducing the weight of plaster materials based on circular economy criteria and the incorporation of waste, such as the addition of polyamide powder waste or plastic cable waste [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Evans et al [12] developed a new method for the preparation of semi-dry plaster mortars, which incorporated expanded perlite with glass fibers. The fact that these lightened plaster materials are easily applicable on site and have good thermal resistance leads to their incorporation as rehabilitation materials, even improving the results obtained with porous materials made with Portland cement [13]. Finally, we find authors who have focused their research on reducing the weight of plaster materials based on circular economy criteria and the incorporation of waste, such as the addition of polyamide powder waste or plastic cable waste [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight porous materials were prepared using DG, NaHCO 3 , and hydroxyethyl methyl cellulose [71]. It was found that by adding hydroxyethyl methyl cellulose, the void fraction of the material was significantly increased.…”
Section: Other Materialsmentioning
confidence: 99%
“…Mainly, the increase in e ringite in the system and the mesh architecture of C-S-H made the architecture more dense, which had a significant effect on the strength enhancement. Lightweight porous materials were prepared using DG, NaHCO3, and hydroxyethyl methyl cellulose [71]. It was found that by adding hydroxyethyl methyl cellulose, the void fraction of the material was significantly increased.…”
Section: Other Materialsmentioning
confidence: 99%
“…To tailor the initial setting time and bolster the mechanical strength of gypsum materials, significant research has focused on their modification, such as the incorporation of organic polymers and inorganic additives into gypsum systems [8][9][10][11][12][13]. Yu et al notably enhanced the toughness and strength of composites by integrating organic and inorganic units at a molecular scale into an inorganic base [14].…”
Section: Introductionmentioning
confidence: 99%